Factors effecting bone mineral density in stroke patients - Tatli, S; Kavuncu, V (B M J Publishing Group, 2003)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 18, 2003 -- LISBON, PORTUGAL